The Innovation Process of Transforming Liquid Param Manna into Cream Param Manna - Yenny Sarwokusumo (Journal of Management and Business Environment (JMBE), 2020)
The purpose of this study is to determine business innovation process transforming Param Kocok Manna into Param Cream Manna to open new business opportunities. The data collection technique in this research was questionnaire. This research concluded that since  the idea generation stage of the innovation process to open a new business was originally from its customers. The products of Param Cream Manna are the innovative products that are highly accepted by the market to create new market opportunities.